CULÍCIDOS (DIPTERA) DEL RÍO CHILLÓN Y SECTORES ADYACENTES DE LA PROVINCIA CONSTITUCIONAL DEL CALLAO, PERÚ, DURANTE EL NIÑO 1997-1998 (Acta Entomológica Chilena, 2022)
The present study evaluated somc areas of natural breeding places of mosquitoes near human populationsin Callao-Perú during December 97 to August 98: Chillón River margins, adjacent areas to underdevelopmenttown “Los Carrizales” and Ventanilla wetlands (Ventanilla district) and underdevelopment towns: Tiwinza,Daniel A. Carrión and Francisco Bolognesi (Carmen de la Legua district), Larvae of culicids of medicalimportance as Anopheles pseudopunctipennis (Theobald), Culex quinquefasciatus (Say) and Aedestaeniorhynchus(Wiedemann) were assessed. A. taeniorhynchus was registered for the first time during August98 at “Los Carrizales” and Ventanilla wetlands in areas with the highcst salinities (39,5%) in comparisonwith the other areas of natural breeding places of mosquitoes. The least water temperatures (21,1 °C) and thehighest pH (7,8) were observed in these localities. Chillón River presenled the highest richness of biologicaltaxa of all localities evaluated. The culicid A. pseudopunctipennis was observed in Chillón River at thehighest air lemperature (28,6 °C) and water temperature (28,1 °C) and the least pH (7,02). Moreover, spatialand temporal variation of population and the larvae índex were observed in nine survey points of ChillónRiver. High larvae indexes of A. pseudopunctipennis were associated with presence of the algae Cladophoraglomerata (L.) Kuelzing and with the macrophyte Lemna minor (L.). The larvivorous fish Poecilia reticulataPelers, nayads of Libellulidae and Coenagrionidae (Odonata) and adults of Dyliscidae (Coleóptera) wererecorded as potential prcdators. The results were compared with those of the 1995-96 Pre-ENSO event,concluding that one of the consequences of Southern Oscillation ENSO “El Niño” 1997-98 event in thePeruvian coast was an increase of the population of these culicids of medical importance.
Keywords: culicids, Anopheles, Aedes, Culex, Callao, ENSO 97-98, environmental condition